Evaluation of the alternative classification criteria of systemic lupus erythematosus established by Systemic Lupus International Collaborating Clinics (SLICC). Issue 4 (4th July 2018) - Oku, Kenji; Atsumi, Tatsuya; Akiyama, Yuji; Amano, Hirofumi; Azuma, Naoto; Bohgaki, Toshiyuki; Asanuma, Yu Funakubo; Horita, Tetsuya; Hosoya, Tadashi; Ichinose, Kunihiro; Kato, Masaru; Katsumata, Yasuhiro; et al.
Abstract: Objective: To evaluate the performance of the 2012 Systemic Lupus International Collaborating Clinics criteria (SLICC-12) on classifying systemic lupus erythematosus (SLE) in an uncontrolled multi-centered study with real-life scenario of the patients in Japan. Methods: This study comprised 495 patients with SLE or non-SLE rheumatic diseases and allied conditions from 12 institutes in Japan. Chart review of each patient was performed by the 27 expert rheumatologists and diagnosis of 487 cases reached to the consensus. Value of the SLICC-12 on SLE classification was analyzed comparing with the 1997 revised American College of Rheumatology SLE classification criteria (ACR-97) employing the expert-consented diagnoses. Results: Compared to the ACR-97, the SLICC-12 had a higher sensitivity (ACR-97 vs. SLICC-12: 0.88 vs. 0.99, p  < .01) and comparable specificity (0.85 vs. 0.80). The rate of misclassification (0.14 vs. 0.11) or the area under the receiver operating characteristic curves (0.863 vs. 0.894) was not statistically different. In the cases that diagnoses corresponded in high rates among experts, both criteria showed high accordance of SLE classification over 85% with the expert diagnoses. Conclusion: Although employment of SLICC-12 for the classification for SLE should be carefully considered, the SLICC-12 showed the higher sensitivity on classifying SLE in Japanese population.